Case Report: Pseudomeningeosis and Demyelinating Metastasis-Like Lesions From Checkpoint Inhibitor Therapy in Malignant Melanoma - Schmidt, Teresa; Kebir, Sied; Livingstone, Elisabeth; Junker, Andreas; Zülow, Stefan; Lazaridis, Lazaros; Oster, Christoph; Chorti, Eleftheria; Pierscianek, Daniela; Pul, Refik; Keyvani, Kathy; Sure, Ulrich; et al. (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have considerably expanded the effective treatment options for malignant melanoma. ICIs revert tumor-associated immunosuppression and potentiate T-cell mediated tumor clearance. Immune-related neurologic adverse events (irNAEs) manifest in the central (CNS) or peripheral nervous system (PNS) and most frequently present as encephalitis or myasthenia gravis respectively. We report on a 47-year old male patient with metastatic melanoma who developed signs of cerebellar disease five weeks after the start of ICI treatment (ipilimumab and nivolumab). Magnetic resonance imaging (MRI) of the brain and spine revealed multiple new contrast enhancements suggestive of parenchymal and leptomeningeal metastasis. Cerebral spinal fluid (CSF) evaluation showed a lymphomononuclear pleocytosis in the absence of tumor cells. Subsequent stereotactic brain biopsy confirmed demyelinating disease. High-dose corticosteroid treatment resulted in immediate improvement of the clinical symptoms. MRI scans and CSF re-evaluation were conducted six weeks later and showed a near-complete remission. The strong resemblance to neoplastic CNS dissemination and irNAEs is a particularly difficult diagnostic challenge. Treating physicians should be aware of irNAEs as those can be effectively treated with high-dose steroids.